Analisis Wacana Kritis terhadap Representasi Gender dalam Iklan L'oréal Paris Elvive Extraordinary Oil - Anindya Gustria Nirwasita; Adis Dewanti Rachmanda (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This study aims to analyze gender representation in the L’Oréal Paris Elvive Extraordinary Oil advertisement using Sara Mills’ Critical Discourse Analysis (CDA) approach. The advertisement functions not only as a promotional medium for hair-care products but also as a site of meaning production that shapes social constructions of beauty, women’s roles, and power relations within society. Through the visuals and narrative presented, women are portrayed as the central focus as well as symbols of ideal beauty, characterized by shiny hair, an elegant appearance, and a confident demeanor. The analysis shows that women in the advertisement are positioned primarily as visual objects, while the L’Oréal Paris brand takes the role of the subject that provides solutions to women’s problems—specifically damaged hair. The use of the iconic slogan “Because you’re worth it” constructs a discourse suggesting that women’s self-worth and personal value are closely tied to physical appearance, especially the condition of their hair. Thus, the advertisement not only delivers commercial messages but also carries ideological implications about beauty standards that women are expected to meet. This study concludes that advertising plays a crucial role in reproducing contemporary gender norms and influences how society interprets women’s identity and value through the visual representations it presents.